Tuesday

September 30, 2014

September 30, 2014

Posted by **Callie** on Friday, January 20, 2012 at 9:06am.

(x-3)^2 + (y+2)^2=25

(x-7)^2 + (y+2)^2=25

(x-7)^2 + (y-7)^2=25

(x-3)^2 + (y-2)^2=25

- Math -
**Steve**, Friday, January 20, 2012 at 11:29amsince the axis of reflection is vertical, the y-coordinates do not change.

(x,y) --> (2-(x-2),y) = (4-x,y)

The old center was (-3,2) so the new center is (7,2)

I don't see that as a choice. Typo in problem?

**Answer this Question**

**Related Questions**

geometry - The equation of a circle is(x-3)squared plus (y+2)squared.The point (...

math - A circle with the equation (x + 4)2 + (y - 3)2 = 9 is reflected over the ...

mathematics - The circle x2-2x+y2-4y-4=0 lies on the cartesian plane,question 2....

mathematics - The circle x2-2x+y2-4y-4=0 lies on the cartesian plane,question 2....

mathematics - The circle x2-2x+y2-4y-4=0 lies on the cartesian plane,question 2....

Math - The point A (-7, 5) is reflected over the line x = -5, and then is ...

Geometry - A circle with the equation (x + 3)2 + (y - 2)2 = 25 is reflected ...

math - i am having a minor difficulty i've been stuck for over an hour and don't...

MATHS - Prove that one over one squared plus one over two squared plus one over ...

Math - Find the equation of a hyperbola of the form x squared / M - y squared / ...